Improved Intrinsic Activity of Ce0.5Pr0.5O2 for Soot Combustion by Vacuum/Freeze-Drying - Li, Qian; Su, Yimin; Liu, Xuesong; Lv, Yanan; Zhang, Nana; Xin, Ying; Zhang, Zhaoliang (Frontiers in Environmental Chemistry, 2021)
Vacuum drying and freeze drying were adopted to improve catalytic activity of Ce0.5Pr0.5O2 for soot combustion. The specific surface area and pore volume of as-prepared Ce0.5Pr0.5O2 were greatly increased compared to the counterpart using the common drying method. Furthermore, the redox performance and the oxidation ability for soot were enhanced, as demonstrated by H2-TPR and Soot-TPR. Thus, lower combustion temperatures and higher intrinsic activity were obtained. This work demonstrated that simply changing drying process of precipitates can be served as a paradigm to improve the structure and catalytic performance.